Next Generation Immunotherapy for Pancreatic Cancer: DNA Vaccination is Seeking New Combo Partners - Cappello, Paola (Cancers (Basel), 2018)
Pancreatic Ductal Adenocarcinoma (PDA) is an almost incurable radio- and chemo-resistant tumor, and its microenvironment is characterized by a strong desmoplastic reaction associated with a significant infiltration of T regulatory lymphocytes and myeloid-derived suppressor cells (Tregs, MDSC). Investigating immunological targets has identified a number of metabolic and cytoskeletal related molecules, which are typically recognized by circulating antibodies. Among these molecules we have investigated alpha-enolase (ENO1), a glycolytic enzyme that also acts a plasminogen receptor. ENO1 is also recognized by T cells in PDA patients, so we developed a DNA vaccine that targets ENO1. This efficiently induces many immunological processes (antibody formation and complement-dependent cytotoxicity (CDC)-mediated tumor killing, infiltration of effector T cells, reduction of infiltration of myeloid and Treg suppressor cells), which significantly increase the survival of genetically engineered mice that spontaneously develop pancreatic cancer. Although promising, the ENO1 DNA vaccine does not completely eradicate the tumor, which, after an initial growth inhibition, returns to proliferate again, especially when Tregs and MDSC ensue in the tumor mass. This led us to develop possible strategies for combinatorial treatments aimed to broaden and sustain the antitumor immune response elicited by DNA vaccination. Based on the data we have obtained in recent years, this review will discuss the biological bases of possible combinatorial treatments (chemotherapy, PI3K inhibitors, tumor-associated macrophages, ENO1 inhibitors) that could be effective in amplifying the response induced by the immune vaccination in PDA.